2019
DOI: 10.3846/jbem.2019.10156
|View full text |Cite
|
Sign up to set email alerts
|

Higher Education Institutions’ Impact on the Economy

Abstract: Despite the strong public interest in the accountability and efficiency in education spending on higher education institutions (HEIs) in Lithuania, there are currently no existing studies which have examined the impact of HEIs on the country’s economy. In the present study, we have used a disaggregated input-output table for Lithuania’s tertiary education institutions in order to determine the output value added to the local economy by the presence of HEIs. The results of the study have revealed that HEIs cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 46 publications
0
9
1
Order By: Relevance
“…The former study paid no attention to the availability of small sale IGAs such as agricultural-based activities. The study by Vaiciukevičiūtė et al (2019) also found out that IGAs have an impact on a country's economy, which is dissimilarity from IGAs targeted by the current study that aimed to supplement public secondary schools' government grants and capitation. Panigrahi (2019) conducted a study in India on the financing the education sector and found out that government-support funds are insufficient to finance education and thus, education institutions suffocate from financial constraints.…”
Section: Review Of Related Literaturecontrasting
confidence: 71%
See 1 more Smart Citation
“…The former study paid no attention to the availability of small sale IGAs such as agricultural-based activities. The study by Vaiciukevičiūtė et al (2019) also found out that IGAs have an impact on a country's economy, which is dissimilarity from IGAs targeted by the current study that aimed to supplement public secondary schools' government grants and capitation. Panigrahi (2019) conducted a study in India on the financing the education sector and found out that government-support funds are insufficient to finance education and thus, education institutions suffocate from financial constraints.…”
Section: Review Of Related Literaturecontrasting
confidence: 71%
“…The review of related literature on examining and exploring the availability of school-based income-generating activities intends to see what scholars have discussed on the matter under discussion at the global and local levels. Vaiciukevičiūtė et al (2019) conducted a study in Lithuania on the impact of the economy on public education institutions. The study aimed to determine how education institutions can substantially impact a country's economy.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Due to the impact of the free movement of labour, on the European market and including in Romania, some vulnerabilities are created for certain categories of workers, especially for those with a low level of education (Gottvald et al, 2013). The importance of education is highlighted in literature (Vaiciukeviciute et al, 2019). According to Eurostat data, the number of workers with higher education in the EU Member States of the European Union in the period 2008-2015 increased by 13 million workers, while the number of those with secondary education decreased by 7.4 million.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Due to the growing role of education in the modern world, more and more studies are being directed to the knowledge-economy sphere, which demonstrates its place change in the national economy and ecology system (Vaiciukevičiūtė et al, 2019, Skliar, 2018, Wierzbicka, 2018, Smaliukienė et al, 2017, Vovk, 2017, Jikia et al, 2017, Balcerzak, 2016, Lyeonov & Liuta, 2016, Matošková, 2016, Marekha, 2016Tamulevičienė & Androniceanu, 2020). In general, many works of the native and foreign scientists were devoted to the study of the relationship between separate indicators of the state policy in the education sector (Kowalska, 2016, Mazurek & Mielcová, 2019, Palascakova et al, 2019.…”
Section: Literature Reviewmentioning
confidence: 99%